Avaliação da atividade citotóxica in vitro do óleo de rã-touro (Rana catesbeiana Shaw) frente ao câncer de pele - Oliveira, Wogenes Nunes de (2019)
Bullfrog oil, an animal oil extracted from the adipose tissue of Rana catesbeiana Shaw, showed promising cytotoxic activity against melanoma cells and, therefore, potential to become a pharmaceutical active compound. However, there is a lack of information regarding the pathways involved its pharmacological activity. Thus, the aim of this study was to investigate and elucidate the cytotoxic effect of this oil against human melanoma cells (A2058). The cytotoxic potential was evaluated by the MTT assay, the cell cycle analysis and the cell death assay. In addition, the apoptotic potential was investigated by (i) the DNA fragmentation using propidium iodide (PI) staining analysis, (ii) the evaluation of mitochondrial membrane potential and (iii) the determination of intracellular reactive oxygen species (ROS) level. The results showed that the bullfrog oil was able to promote a time-dependent cytotoxic effect, decreasing cell viability in 38 % after 72 hours of treatment without affecting the cell cycle. Additionally, the bullfrog oil induced the apoptosis in A2058 cells, increasing up to 50 ± 13 % the intracellular ROS level, maintaining the DNA integrity and promoting an approximate decrease of 35 ± 5 % in the mitochondrial membrane potential. It can be concluded that the in vitro cytotoxic effect of the bullfrog oil in human melanoma cells is mediated by oxidative stress that induces mitochondrial dysfunction, triggering the apoptosis. These unprecedented results highlight the pharmacological potential of bullfrog oil and provide important information to support studies on the development of new pharmaceutical products for complementary and alternative treatments for melanoma.